2020
DOI: 10.1096/fj.202000264
|View full text |Cite
|
Sign up to set email alerts
|

Porcine arterial ECM hydrogel: Designing an in vitro angiogenesis model for long‐term high‐throughput research

Abstract: The field of angiogenesis research provides deep understanding regarding this important process, which plays fundamental roles in tissue development and different abnormalities. In vitro models offer the advantages of low‐cost high‐throughput research of angiogenesis while sparing animal lives, and enabling the use of human cells. Nevertheless, prevailing in vitro models lack stability and are limited to a few days' assays. This study, therefore, examines the hypothesis that closely mimicking the vascular micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…We expected that given both 3-component formulations exhibited comparable G', G" and Y modulus (Fig 2A and B), the 4-component mix would present similar mechanical properties. Surprisingly, this was not confirmed experimentally, and the four-component mix showed a significant increase in both storage and loss modulus (Fig 2A ), to reach values reported by Davidov et al 40 where they prepared a ECM matrix from decellularized arterial tissue which showed higher efficiency in generating stable angiogenic-type growth in the standard in vitro assay. This significant increase in terms of stiffness was confirmed in compression tests with nearly a two-fold increase in Young modulus from approximately 2 kPa for the 3-component hydrogels to 4 kPa for the 4-component hydrogel (Fig 2B), also consistent with values reported by others 41,42 .…”
Section: Figure S3 Cell Viability Of Epcs Encapsulated Within 3 Diffe...mentioning
confidence: 60%
See 2 more Smart Citations
“…We expected that given both 3-component formulations exhibited comparable G', G" and Y modulus (Fig 2A and B), the 4-component mix would present similar mechanical properties. Surprisingly, this was not confirmed experimentally, and the four-component mix showed a significant increase in both storage and loss modulus (Fig 2A ), to reach values reported by Davidov et al 40 where they prepared a ECM matrix from decellularized arterial tissue which showed higher efficiency in generating stable angiogenic-type growth in the standard in vitro assay. This significant increase in terms of stiffness was confirmed in compression tests with nearly a two-fold increase in Young modulus from approximately 2 kPa for the 3-component hydrogels to 4 kPa for the 4-component hydrogel (Fig 2B), also consistent with values reported by others 41,42 .…”
Section: Figure S3 Cell Viability Of Epcs Encapsulated Within 3 Diffe...mentioning
confidence: 60%
“…Rheological characterizations of photopolymerized 3- and 4-component hydrogel structures using either frequency-dependent oscillatory rheological analysis (A) or compression tests (B). *,**:Boxed areas correspond to modulus values of related ECM matrices published in (A) reference 40 and in (B) references 41,42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain stable pECM hydrogels, dry pECM at concentrations, as detailed in Table 1 , was solubilized in HCl (0.01 M) using 1 min sonication, followed by enzymatic digestion using pepsin (1-5 mg ml −1 , Sigma-Aldrich, St. Louis, MO, USA). The pH of the solution was then elevated using NaOH and kept cold (4 °C), as previously described [ 9 , 63 , 64 ]. To allow the thermally-induced self-assembly of the hydrogels, solubilized samples were plated for 1 hr at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…EcM-G is a class of naturally derived proteinaceous biomaterials, with excellent biophysical, biomechanical, and biochemical properties, which can provide biological signals and maintain tissue microarchitecture for guiding on cell growth, differentiation, neovascularization and functional improvement (16). It has been shown that collagen and elastin, both of which are the most abundant proteins in the EcM-G, played a critical role in controlling tissue osmotic pressure and regulating intracellular signaling cascades that direct stem cell differentiation and function (17,18).…”
Section: Ecm-g Characterizationmentioning
confidence: 99%